Screening the impact of food co-digestion on lipolysis under sub-optimal intestinal conditions. (January 2020) - Calvo-Lerma, Joaquim; Asensio-Grau, Andrea; Heredia, Ana; Andrés, Ana
Abstract: The scarce literature about the effect of meal-factors have on lipids digestibility encouraged the present study, in which olive oil was co-digested with naturally fat-free matrices that were rich in carbohydrate (potato and bread) or protein (degreased fresh cheese, hake and turkey) in single, binary and ternary combinations. Digestion was simulated in vitro, and the effect of co-digestion on the release of free fatty acid (FFA) from oil lipolysis were measured by gas chromatography-mass spectrometry. Regarding total FFA release, higher values were found in carbohydrate-rich systems, especially in potato, than in those with protein matrices. Thus, when co-digesting a carbohydrate matrix in addition to one or two protein matrices, lipolysis was reduced. This finding was explained by the carbohydrate and protein ratio of the resulting combinations, as the release of FFA increased with the carbohydrate/protein ratio (R 2 = 0.87, p < 0.001 in potato; R 2 = 0.81, p = 0.04 in bread systems). This study supposes the first approach towards characterisation of lipid digestion regarding food matrix nutritional composition. Highlights: Co-digestion of olive oil lipids with carbohydrate- or protein-rich food matrices has been characterised. Total free fatty acid release is higher when oil is co-digested with carbohydrate-rich matrices. Protein-rich matrices allow for lower total FFA release. Lipolysis is linearly correlated with the carbohydrate/protein ratio in the resulting digestion system.